METODE SEDERHANA UNTUK MENCEGAH TERJADINYA PUKULAN AIR DI DALAM INSTALASI PLAMBING - - Murni (TRAKSI, 2007)
Blow irrigite because of the happening of increas of high pessure on the spur of the moment effect of closing of spillway sudden., this blow will result damage in instalation of plumbing, to avoid this matter at instalation of plumbing needed by an appliance silencer of simplest blow among others cheap and of its price is to install air cavity in place is where enabled by the happening of water blow.   Keyword : Plumbing, dir causty, dilencer